Predicting the geographical distributions of the macaque hosts and mosquito vectors of Plasmodium knowlesi malaria in forested and non-forested areas - Moyes, Catherine L.; Shearer, Freya M.; Zhi, Huang; Wiebe, Antoinette; Gibson, Harry S.; Nijman, Vincent; Jayasilan, Mohd-Azlan; Jedediah, F. Brodie; Suchinda, Malaivijitnond; Linkie, Matthew; Hiromitsu, Samejima; O’Brien, Timothy G.; et al. (BioMed Central Ltd., 2016)
Background: Plasmodium knowlesi is a zoonotic pathogen, transmitted among macaques and to humans by anopheline mosquitoes. Information on P. knowlesi malaria is lacking in most regions so the first step to understand the geographical distribution of disease risk is to define the distributions of the reservoir and vector species.